Food diversity and compliance of menus with nutritional recommendations of kindergartens in İstanbul - AKTAÇ, ŞULE (My University, 2023)
This descriptive research was carried out in randomly selected 210 kindergartens in 7 districts sides of Istanbul. The study aimed to examine the characteristics of preschool menus and compare them to the nutritional requirements of children. Meals served in breakfast, lunch, and snacks were determined in portions and nutritional and energy content is calculated. The nutrient content of the menus was compared to Dietary Guidelines for Turkey to meet the daily requirements. 21.4% of the kindergartens that provided food reported that dietitians planned the menu. The mean percentages of meeting the daily energy recommendations for breakfast, lunch, and afternoon meals were 26.18%, 29.54%, and 6.48% respectively. Of those kindergarten menus were most convenient for consumption (94.3%); they provided a variety in terms of consistency (85.2%) and pattern variety (68.1%). The dietary fiber content of the menus was insufficient compared to the daily recommendations. The menus offer sweetened fruit juices, and salads were less served than recommendations. Kindergarten menus should contain more whole grains and vegetables to provide requirements for dietary fiber.

Tanımlayıcı türde olan bu araştırma, İstanbul'un 7 ilçesinde rastgele seçilen 210 anaokulunda yürütülmüştür. Çalışma, okul öncesi menülerin özelliklerini incelemeyi ve çocukların beslenme gereksinimleriyle karşılaştırmayı amaçlamıştır. Kahvaltı, öğle yemeği ve ara öğünlerde verilen öğünlerin porsiyonları belirlenerek enerji ve besin ögesi içerikleri hesaplanmıştır. Menülerin besin içeriklerinin, günlük gereksinimlerinin karşılama durumu Türkiye Beslenme Rehberi’ ile karşılaştırılmıştır. Anaokullarının %21,4'ünde menünün diyetisyenler tarafından planlandığı görülmüştür. Kahvaltı, öğle yemeği ve ikindi öğünleri menülerinin günlük enerji tavsiyelerini karşılama yüzdelerinin ortalamaları sırasıyla %26,18, %29,54 ve %6,48'dir. Anaokulu menülerinin; %94,3’ü tüketim açısından ve %85,2’si kıvam açısından uygun olup, %68,1’i örüntü açısından çeşitlilik sağlamıştır. Menülerin posa içeriği günlük önerileri karşılamada yetersiz olduğu saptanmıştır. Menüler, yüksek sıklıkta ilave şeker içeren hazır meyve suları ve düşük sıklıkta salata içermektedir. Anaokulu menüleri, diyet lifi ihtiyacını karşılamak için daha fazla tam tahıl ve sebze içermelidir.
İstanbul’da Bulunan Anaokulu Menülerinin Beslenme Önerilerine Uygunluğu ve Yemek Çeşitliliği
Keywords: Beslenme ve Dietetik; Sağlık Bilimleri; Nutrition and Dietetics; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; BESLENME VE DİYETETİK; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; Beslenme ve Diyetetik